Analisis Perbedaan Kinerja Keuangan Sebelum dan Sesudah Go Publik pada PT. Samator Indo Gas di Bursa Efek Indonesia - Tiara Nurbayiti Ibrahim; Gaffar; Amir Lukum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze and test differences in financial performance at PT. Samator Indo Gas before and after going public using CR, DER, ROI and TATO ratios. This study uses a quantitative approach. The population is the financial reports at PT. Samator Indo Gas. The sampling applies purposive sampling. The samples are financial reports 5 years before going public and 5 years after going public. The data analysis research is by testing ratio analysis, normality test, difference test (T test). The results show a significant difference in financial performance at PT. Samator Indo Gas before and after going public seen from the DER ratio. And there is no significant difference in financial performance at PT. Samator Indo Gas before and after going public as seen from the CR, ROI and TATO ratios.